2018
DOI: 10.1093/jamia/ocy134
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a web-based educational program for veterans who read their mental health notes online

Abstract: Objective This study evaluates whether a web-based educational program for patients who read their mental health notes online improves patient-clinician communication and increases patient activation. Methods The web-based educational program, developed with end-user input, was designed to educate patients on the content of mental health notes, provide guidance on communicating with clinicians about notes, and facilitate pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“… 20 , 21 Another study found these benefits could be further increased through patient education programs. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Another study found these benefits could be further increased through patient education programs. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In cases in which ethics consultation notes will be made available in the patient portal, consultants can mitigate potential challenges by adapting guidance from clinicians with experience sharing notes 29,31,33,34,35 and by taking certain precautionary steps before, during, and after documentation.…”
Section: Practical Documentation Strategiesmentioning
confidence: 99%
“…As an asynchronous communication tool, open notes can serve as an online extension of the visit, helping improve a sense of control and engagement with care. This may be especially important for offering reassurance to patients with long COVID whose symptoms are still poorly understood [24,25]. 6. Working under the considerable pressures wrought by the pandemic, it is not yet known whether patient safety has been negatively affected by human error [9].…”
mentioning
confidence: 99%